THE LINGUOCULTURAL CHARACTERISTICS OF ENGLISH AND UZBEK FOLK TALES - Tursunbayeva Shaxnoza (Research Focus International Scientific Journal, 2025)
This study explores the linguocultural characteristics of English and Uzbek folk tales, examining how language and culture are intertwined in shaping the narrative structures, themes, and moral lessons of these two distinct traditions. By analyzing the linguistic features, cultural values, and storytelling practices, this research highlights the ways in which language reflects the worldview of each culture. The study also compares the role of oral traditions, religious influences, and the universality of themes such as good versus evil, illustrating how these stories, while sharing common elements, are deeply shaped by their cultural contexts.